Projeto conceitual de um sistema de câmbio mecânico de bicicleta comandado eletronicamente - Medeiros, Alisson Luiz de (Universidade Federal Rural do Semi-Árido, 2019)
The work aims to develop a conceptual form of solution for the inconsistency and inaccuracy in gear shifting, complete with the change of time when in an environment with extreme conditions such as rain, mud and dust. From the conceptual design, it is also possible to solve a problem of the high added value of an electronic bicycle route manufactured by major brands, which makes it impossible to access components of a bicycle with low purchasing power. The main types of movement are nowadays in the market and its evolution over time is also highlighted in the components that make up the bicycle, highlighting the change of direction from the conceptual model of electronically controlled mechanical gear. For the development of a project methodology developed by MUNARI that enabled the production of a conceptual project as a solution to the problem.
Monografia
Keywords: Câmbio; Bicicleta; Evolução; Desenvolvimento; Componentes; Custo; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA